2013
DOI: 10.2807/1560-7917.es2013.18.50.20660
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hantavirus infections in Switzerland in 2009: difficulties in determining prevalence in a country with low endemicity

Abstract: In several European countries, diagnosis of nephropathia epidemica, a mild form of haemorrhagic fever with renal syndrome (HFRS) caused by Puumalavirus infection, has increased over the past 10-20 years. In Switzerland, despite its geographical proximity to regions with epidemic outbreaks in Germany and France, infections are detected only sporadically. To estimate the actual prevalence and potential risk factors of human hantavirus infections in Switzerland, a seroepidemiological study was performed in 2009 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In our study, the high rate of positive IgG antibodies by ELISA shown here could be false‐positive, originating from the sensitivity of the screening test. Moreover, the difference between ELISA and confirmatory assays has been shown in several orthohantavirus seroprevalence studies (Engler et al, ; Sevancan et al, ). The different results by immunoblotting and IIFT can be explained by sensitivity (immunoblotting—96.1%, IIFT—99%) and specificity (immunoblotting—100%, IIFT—98%) of the used assays (mikrogen.de, euroimmun.de).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the high rate of positive IgG antibodies by ELISA shown here could be false‐positive, originating from the sensitivity of the screening test. Moreover, the difference between ELISA and confirmatory assays has been shown in several orthohantavirus seroprevalence studies (Engler et al, ; Sevancan et al, ). The different results by immunoblotting and IIFT can be explained by sensitivity (immunoblotting—96.1%, IIFT—99%) and specificity (immunoblotting—100%, IIFT—98%) of the used assays (mikrogen.de, euroimmun.de).…”
Section: Discussionmentioning
confidence: 99%
“…The different results by immunoblotting and IIFT can be explained by sensitivity (immunoblotting—96.1%, IIFT—99%) and specificity (immunoblotting—100%, IIFT—98%) of the used assays (mikrogen.de, euroimmun.de). However, immunoblotting assay is used as more suitable diagnostic and confirmatory test (Engler et al, ; Escadafal et al, ). In the Almaty region some rodent studies were conducted, in which in some areas rodents were found to be positive for orthohantaviruses, but no clinical case of HFRS has officially been registered in this region so far (Plyusnina et al, ; Sutyagin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for this discrepancy may be that human cases are being missed because local doctors do not know enough about NE. Several serological studies have already suggested that large numbers of undiagnosed human Hantavirus infections occur in various countries [ 38 , 39 , 40 , 41 , 42 ]. However, we think that a significant number of serious cases of NE would undoubtedly have led to medical investigations and more accurate diagnosis, so this possibility seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…For ELISA testing, the use of >1.1 OD cut-off has been previously questioned with a preference for a more stringent cutoff of >2.0 being advanced to avoid the high number of false positives [ 70 , 71 ]. From the orthohantavirus-seropositive patients ( n = 861), samples were selected for confirmatory testing ( n = 157) using criteria for further confirmatory testing which entailed having orthohantavirus-seropositive IgM test results, less than two years of frozen storage and sufficient available sample volume ( Figure 1 A).…”
Section: Methodsmentioning
confidence: 99%